2001
DOI: 10.1002/cne.1372
|View full text |Cite
|
Sign up to set email alerts
|

“Type III” cells of rat taste buds: Immunohistochemical and ultrastructural studies of neuron‐specific enolase, protein gene product 9.5, and serotonin

Abstract: Taste buds contain a variety of morphological and histochemical types of elongate cells. Serotonin, neuron-specific enolase (NSE), ubiquitin carboxyl terminal hydrolase (PGP 9.5), and neural cell adhesion molecule (N-CAM) all have been described as being present in the morphologically defined Type III taste cells in rats. In order to determine whether these substances coexist in a single cell, we undertook immunohistochemical and ultrastructural analysis of taste buds in rats. Double-label studies show that PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
270
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(285 citation statements)
references
References 39 publications
14
270
1
Order By: Relevance
“…NCAM and serotonin antisera were used to assess BMP4-ß-gal expression in type III cells (Figure 3E,E',F,F'), and 8% of serotonin-IR cells and 12.5% of NCAM-IR cells were ß-gal-immunopositive (Figure 3G). Finally, PGP9.5 antiserum recognizes a subset of both type II and III cells, which are not immunoreactive for gustducin or serotonin, respectively [17]. Double immunolabeling for ß-gal and PGP9.5 revealed that 11.7% of PGP9.5-IR expressing cells also were ß-gal-IR (Figure 3D,D',G).…”
Section: Resultsmentioning
confidence: 99%
“…NCAM and serotonin antisera were used to assess BMP4-ß-gal expression in type III cells (Figure 3E,E',F,F'), and 8% of serotonin-IR cells and 12.5% of NCAM-IR cells were ß-gal-immunopositive (Figure 3G). Finally, PGP9.5 antiserum recognizes a subset of both type II and III cells, which are not immunoreactive for gustducin or serotonin, respectively [17]. Double immunolabeling for ß-gal and PGP9.5 revealed that 11.7% of PGP9.5-IR expressing cells also were ß-gal-IR (Figure 3D,D',G).…”
Section: Resultsmentioning
confidence: 99%
“…They extend microvilli from their tapered apical surface into the taste pit and pore, which reflect a small, recessed opening in the surrounding epithelium. On the basis of microscopic features and specific markers, the sensory cells of taste buds are presently categorized as type II or type III cells, whereas the supporting cells are referred to as type I cells [40][41][42]. A majority of the sensory cells in taste buds are type II cells, which are believed to detect bitter, sweet and umami stimuli [42,43].…”
Section: Espins In the Microvillar Processes Of Other Sensory Cellsmentioning
confidence: 99%
“…2D, arrowheads). Type III cells appear to represent a relatively minor population of taste bud cells and are believed to display a single blunt apical microvillus that projects far up into the taste pore [41,44,45] (fig. 2D, arrow).…”
Section: Espins In the Microvillar Processes Of Other Sensory Cellsmentioning
confidence: 99%
“…1,[5][6][7] To determine which types of cells express Fxyd6 in CV taste buds, we carried out double-labeled in situ hybridization. Trpm5 and Pkd2l1 were used as cell markers in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Type III cells have synaptic vesicles including synaptic molecules and express the channels for sour taste. 1,5,7,8) Type II and III taste cells are known to be electrically excitable, 9) but the sodium ion (Na þ ) channel isoforms expressed by the 2 cell types differ. 10) Type II cells express Na þ channels (SCNs) SCN2A, SCN3A, and SCN9A, whereas type III cells express only SCN2A.…”
mentioning
confidence: 99%